Networked : a contemporary history of news in transition - Russell, Adrienne (Cambridge, UK : Polity Press, 2011)
The contemporary death and life of journalism is the story of an historic cultural transition. We have lived through the end of the mass-media era and the beginning of the networked-media era. We took in news one way for a century and we simply don't do it like that anymore.'Networked' examines this moment in journalism.
Includes bibliographical references and index.
Keywords: Online journalism; Journalism; Digital media